2008
DOI: 10.1128/jvi.01712-07
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus A/HK/483/97(H5N1) NS1 Protein Induces Apoptosis in Human Airway Epithelial Cells

Abstract: Avian H5N1 influenza virus causes a remarkably severe disease in humans, with an overall case fatality rate of greater than 50%. Human influenza A viruses induce apoptosis in infected cells, which can lead to organ dysfunction. To verify the role of H5N1-encoded NS1 in inducing apoptosis, the NS1 gene was cloned and expressed in human airway epithelial cells (NCI-H292 cells). The apoptotic events posttransfection were examined by a terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick-end-labeling ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 60 publications
4
96
1
Order By: Relevance
“…The viral neuraminidase protein was the first influenza virus protein shown to have a role in the induction of apoptosis (Schultz-Cherry & Hinshaw, 1996). The NS1 protein has also been shown to have proapoptotic features (Lam et al, 2008;Schultz-Cherry et al, 2001). However, these data conflict with the finding that NS1 has anti-apoptotic functions (Ehrhardt et al, 2007;Shin et al, 2007c;Zhirnov et al, 2002).…”
Section: Introductioncontrasting
confidence: 55%
“…The viral neuraminidase protein was the first influenza virus protein shown to have a role in the induction of apoptosis (Schultz-Cherry & Hinshaw, 1996). The NS1 protein has also been shown to have proapoptotic features (Lam et al, 2008;Schultz-Cherry et al, 2001). However, these data conflict with the finding that NS1 has anti-apoptotic functions (Ehrhardt et al, 2007;Shin et al, 2007c;Zhirnov et al, 2002).…”
Section: Introductioncontrasting
confidence: 55%
“…However, the cellular signals leading to apoptosis are varied and may depend on the viral strain and the cell type. The influenza virus M1, NS1, and NA proteins have been reported to be related to apoptosis induction [13,16,30]. Also the importance of HA in apoptotic cell death in vitro is further supported by recent findings showing that the HA of the 1918 pandemic influenza virus enhances mortality in mice [11,18,26].…”
Section: Discussionmentioning
confidence: 93%
“…Apoptosis induced by influenza viruses has been shown in a variety of cell lines [21,29,30]. Several viral factors, including M1, NS1, and NA proteins, have been reported to be related to apoptosis induction [13,16,30]. It has been observed that extensive budding of the virus particles on the membrane surface of the infected cells may cause cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…22 Transfection of NS1 from the A/HK/483/97(H5N1) strain into human airway epithelial cells can also induce apoptosis. 23 However, in another report, the ectopic expression of PR8/NS1 protein was shown to produce an antiapoptotic response in MDCK cells through the activation of the PI3K/Akt signaling pathway. 24 In our study, although H5N1-NS1 variants affected IFN induction, the TNFa response and p53 activity, they did not significantly promote or inhibit the apoptosis of Hela cells.…”
Section: Effects Of H5n1-ns1 Variants On Ifn Inductionmentioning
confidence: 99%
“…Given that the relationship between influenza A virus, NS1 and apoptosis has been described in a number of studies, [22][23][24] we compared the effects of different H5N1-NS1 variants on the apoptotic response of Hela cells. As seen in Figure 6a, although the percentage of both earlyapoptotic cells (which possess a single-positive staining pattern detected by FITC-labeled annexin V) and late-apoptotic/necrotic cells (annexin V/PI double-positive staining pattern) were mildly elevated upon expression H5N1-NS1 variants relative to the controls, release of monoor oligonucleosomes from apoptotic cells was unchanged (Figure 6b).…”
Section: H5n1-ns1 Variants Had No Significant Influence On the Apoptomentioning
confidence: 99%